Correlation of platelet activating factor and age-related macular degeneration. (September 2014) - Nitoda, Eirini; Koutsilieris, Michael; Brouzas, Dimitrios; Koutsandrea, Chryssanthi; Philippou, Anastasios; Ladas, Dimitrios; Moschos, Marilita M
<x xml:space="preserve">Abstract</x> Objective: To investigate the role of Platelet Activating Factor (PAF) in the pathogenesis and development of Age-Related Macular Degeneration (ARMD). Research design and methods: Fifty six patients with ARMD (24 patients with dry ARMD and 32 patients with wet ARMD) and 25 age-matched control participants underwent ophthalmological examination, including visual acuity measurement and evaluation of the retina. The participants were classified into three groups according to their retinal status, based on indirect fundoscopy, Optical Coherence Tomography and fluorescein angiography findings. In order to evaluate the concentrations of PAF in serum, blood samples were collected from all participants and were analyzed with ELISA technique. Results: The concentrations of PAF differed significantly according to macular lesions and were found to be lower in patients with ARMD than control participants. Conclusions: PAF levels are decreased along with the severity of ARMD. Understanding the role of PAF in pathogenesis of ARMD could be the impetus for the development of new therapies field of treatment of ARMD or even other retinal diseases.